Assessment of Households’ Perception Towards Participatory Forest Management the Case of Heban Arsi Woreda, Ethiopia - Gonche GIRMA (International Journal of Environmental, Sustainability, and Social Science, 2023)
Understanding the perceptions of local communities towards participatory forest management (PFM) is essential for successful improvements of PFM regarding forest conservation and livelihood improvement. However, there is a lack of research evidence on the perception of local communities for PFM intervention. To better understand the local communities’ perception of PFM, 131 households were surveyed. Data were collected through the household survey; key informant interviews (KIIs), focus group discussion (FGD), and analyzed using descriptive statistics. Results show that the households perceived that there is no deforestation due to the intervention of PFM which leads increment of species diversity, increasing of forest coverage, increased productivity of the forest, and increase valuable species. Respondents also perceived that the PFM has opportunities to change a negative attitude to a positive through giving of power to the local community, enables bounded members, bringing the right to exclude non-PFM members, creates a sense of belongingness, and encourage the right to use the forest products. The finding demonstrated forest income was second contributor of household income among income sources. Actions such as better protection of existing forests to avoid overuse, access to alternative livelihood diversification, better access to market, access to better skills and knowledge on the collection and use of forest products and reforestation were suggested to increase the existing benefits and management of PFM. The finding of the study suggests further improvement of local communities’ perception and attitudes as well as providing alternatives to improve forest conditions and livelihood.